Exploring peer education for migrant informal caregivers of mentally ill loved ones: a realist evaluation protocol - Hollaar, Malin; Kocken, Paul; Uysal-Bozkir, Özgül; Smedts, Maria; Denktaş, Semiha (Frontiers in Public Health, 2025)
IntroductionInformal caregivers with a migration background who care for someone with a mental illness often experience elevated caregiver burdens due to factors such as discrimination, language barriers, and stigma. In The Netherlands, a peer education intervention called ‘They Are not Mental?!’ (TANM) addresses these challenges by reducing stigma, increasing help-seeking behaviors, and improving access to healthcare. This transdisciplinary study evaluates how contextual factors and mechanisms influence its outcomes.DescriptionThis research protocol outlines a realist evaluation of the intervention using a mixed-methods design, including interviews, post-questionnaires, and observations. The study will develop and refine the program theory to determine for whom, in what contexts, why, and how the intervention works.DiscussionThis protocol shows how we plan to investigate how, why, for whom and under what circumstances TANM produces its intended outcomes, using a realist evaluation approach. This approach is well-suited for evaluating complex interventions because it accommodates for dynamic and iterative interventions. Its focus is on understanding patterns and mechanisms within specific contexts, using program theories.ConclusionThe evaluation of TANM will inform future intervention adaptations and guide future efforts to support vulnerable populations, particularly migrants navigating caregiving challenges.